Criteria for priority-setting in health care in Uganda: exploration of stakeholders' values - Kapiriri Lydia; Norheim Ole Frithjof (The World Health Organization, 2004)
OBJECTIVE: To explore stakeholders' acceptance of criteria for setting priorities for the health care system in Uganda. METHODS: A self-administered questionnaire was used. It was distributed to health workers, planners and administrators working in all levels of the Ugandan health care system. It was also distributed to members of the public. Participants were asked how strongly they agreed or disagreed with 18 criteria that could be used to set priorities for allocating health care. A total of 408 people took part . Data were entered and analysed using SPSS statistical software. Predetermined cut-off points were used to rank the criteria into three different categories: high weight (>66% of respondents agreed), average weight (33-66% of respondents agreed) and low weight (<33% of respondents agreed). We also tested for associations between respondents' characteristics and their degree of agreement with the criteria. FINDINGS: High-weight criteria included severity of disease, benefit of the intervention, cost of the intervention, cost-effectiveness of the intervention, quality of the data on effectiveness, the patients age, place of residence, lifestyle, importance of providing equity of access to health care and the community's views. The average-weight criteria included the patient's social status, mental features, physical capabilities, political views, responsibilities for others and gender. Low-weight criteria included the patient's religion, and power and influence. There were few associations between respondents' characteristics and their preferences. CONCLUSION: There was a high degree of acceptance for commonly used disease-related and society-related criteria. There was less agreement about the patient-related criteria. We propose that average-weight criteria should be debated in Uganda and other countries facing the challenge of distributing scarce health care resources.